Rancang Bangun Aplikasi Pembelajaran Matriks Berbasis Web Dengan Model Multimedia Learning (Studi Kasus : SMAN 4 Surabaya) - Prastyawan, Joane Indra; Sunarto, M. J. Dewiyani; Arifin, Mochammad (Jurnal JSIKA, 2012)
Early today, the development of information technology is growing fast, and no more limit for newspaper, audio visual, and electronic. Based on the results of survey that have did by the writer on mathematic subject in odd semester of XII science class at SMAN 4 Surabaya have get a data that 55% from 120 students are still have average score less than 60 for matrix subject, and beside that a bored on this subject because there weren’t interactive class when this subject is running as standard comprehension of the subject has teached. One of the subject that carry out this information technology development is education subject, that’s using web on learning. So, there is a chance to build a design of learning application based on web by multimedia learning model. Based on the system evaluation of testing and questionaire are did, that average for each scoring criteria from three criterias have scored that shows 30% of average for the “very good” scoring criteria, 60% for the “good” scoring criteria, 10% for the “bad” scoring criteria. So, the matrix learning application based on web by model multimedia learning model can be used at SMAN 4 Surabaya and obtained learning result well. Keywords: Learning, Matrix, Web, Multimedia Learning, Information Technology